ANALISIS SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS UNTUK PENGENDALIAN INTERN KAS PADA PD. BPR BANK JOMBANG - Widodo, Heru; Latifah, Nurul (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2016)
Bank as an institution in the field of finance, of course, in everyday activities can not be separated from the transaction receipts and disbursements. Cash as a means of payment that liquid must be managed properly to avoid abuses over the cash. Diversion of the cash can be avoided by the existence of an accounting information system of cash receipts and payments is good. With the information systems and internal controls are satisfactory for cash, then the things that hurt the company can be avoided or at least can be limited to a minimum. This study aimed to analyze the accounting information system cash receipts and disbursements for the internal control of cash in PD. BPR Bank Jombang. In this research, the researcher  using descriptive qualitative data analysis methods. The results of this study is to indicate that the accounting information system cash receipts and disbursements for the internal control of cash in PD. BPR Bank Jombang is good. It is caused due to the implementation of accounting information systems cash receipts and payments are in accordance with the standard operating procedures of the company. In the implementation of the procedure, any cash receipts and disbursements must be accompanied by documents that have been provided by the company as proof of the transaction. And for the internal control of cash the company carried out an external audit once a year to prevent misuse of the company's cash.